2021
DOI: 10.1099/ijsem.0.004763
|View full text |Cite
|
Sign up to set email alerts
|

Motilimonas cestriensis sp. nov., isolated from an inland brine spring in Northern England

Abstract: A novel slightly halophilic Gram-stain-negative bacterial strain (MKS20T) was isolated from a brine sample collected from one of the Anderton brine springs in the Cheshire salt district, located in Northern England. Phylogenetic analysis of the 16S rRNA gene sequence revealed a close proximity to Motilimonas eburnea (98.30 %), followed by Motilimonas pumila … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…pumila PLHSC7‐2 (95.3% identity) (Wang et al ., 2019), along with three unidentified bacterial strains (B01, D12 and A11) isolated from the coastal marine sediment (Jinjun et al ., 2013). In line with previous results of 16S rRNA tree placements (Ling et al ., 2017; Kelbrick et al ., 2021), our Motilimonas clade further formed a cluster proximal to the Psychromonas clade (bootstrap 1.0; average identity <93%) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…pumila PLHSC7‐2 (95.3% identity) (Wang et al ., 2019), along with three unidentified bacterial strains (B01, D12 and A11) isolated from the coastal marine sediment (Jinjun et al ., 2013). In line with previous results of 16S rRNA tree placements (Ling et al ., 2017; Kelbrick et al ., 2021), our Motilimonas clade further formed a cluster proximal to the Psychromonas clade (bootstrap 1.0; average identity <93%) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 91%
“…Our results showed that the 16S rRNA based Maximum‐likelihood (ML) tree firmly place the strain E26 into a clade formed by the three validly published Motilimonas species (bootstrap >0.7) including M . cestriensis MKS20 (98.8% identity) (Kelbrick et al ., 2021), M . eburnea YH6 (97.0% identity) (Ling et al ., 2017) and M .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations